2022
DOI: 10.1007/s11239-022-02643-3
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic prevention and anticoagulant therapy during the COVID-19 pandemic: updated clinical guidance from the anticoagulation forum

Abstract: Thromboembolism is a common and deadly consequence of COVID-19 infection for hospitalized patients. Based on clinical evidence pre-dating the COVID-19 pandemic and early observational reports, expert consensus and guidance documents have strongly encouraged the use of prophylactic anticoagulation for patients hospitalized for COVID-19 infection. More recently, multiple clinical trials and larger observational studies have provided evidence for tailoring the approach to thromboprophylaxis for patients with COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 46 publications
3
53
0
4
Order By: Relevance
“…Our analysis including recently published RCTs [ 25 , 53 , 54 , 56 ] confirmed the main finding of previous meta-analyses [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] and endorsed the current guidelines ( Table S3 in Supplementary Material ) [ 80 , 81 , 82 , 83 ]. On the basis of our results, we cannot advocate for the routine use of therapeutic dose thromboprophylaxis in all COVID-19 patients either.…”
Section: Conclusion and Implications For Practice And Researchsupporting
confidence: 86%
“…Our analysis including recently published RCTs [ 25 , 53 , 54 , 56 ] confirmed the main finding of previous meta-analyses [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ] and endorsed the current guidelines ( Table S3 in Supplementary Material ) [ 80 , 81 , 82 , 83 ]. On the basis of our results, we cannot advocate for the routine use of therapeutic dose thromboprophylaxis in all COVID-19 patients either.…”
Section: Conclusion and Implications For Practice And Researchsupporting
confidence: 86%
“…Three of the meta-analysis concluded that full-dose anticoagulation was associated with an increased risk of bleeding [ 22 24 ]. Expert consensus and guidance suggest therapeutic intensity anticoagulation for moderately ill hospitalized patients at risk of disease progression defined by supplemental oxygen requirement and an elevated D-dimer (> 2–4 times the upper limit of normal range) who are not at risk for anticoagulant-related bleeding [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer levels have been found to be generally higher in critically ill patients than in mild patients (2.4 vs. 0.5 mg/L) ( 122 ). Standard doses of thromboprophylaxis are recommended for adults who are critically ill during hospitalization ( 123 ). Although guidelines for clinical inpatients recommend only standard or therapeutic doses, intermediate doses (defined as low molecular weight heparin bid or increased weight-based dosing that is less than the recommended therapeutic dose) are often used in clinical trials ( 123 , 124 ).…”
Section: Therapymentioning
confidence: 99%
“…Standard doses of thromboprophylaxis are recommended for adults who are critically ill during hospitalization ( 123 ). Although guidelines for clinical inpatients recommend only standard or therapeutic doses, intermediate doses (defined as low molecular weight heparin bid or increased weight-based dosing that is less than the recommended therapeutic dose) are often used in clinical trials ( 123 , 124 ). Drug distribution and metabolic clearance in patients with obesity may necessitate adjustments to dosing.…”
Section: Therapymentioning
confidence: 99%